Assessment of Intraoperative of Range of Motion after Total Ankle Replacement: Radiographic Cohort Study. Issue 4 (22nd October 2020) - Bitar, Rogerio C.; Caolo, Kristin C.; Saito, Guilherme H.; Kim, Jaeyoung; Deland, Jonathan T.; Ellis, Scott J.; Demetracopoulos, Constantine A.; Bitar, Rogerio C.
Category: Ankle Arthritis Introduction/Purpose: One of the proposed benefits of total ankle replacement (TAR), when compared to ankle fusion is the restoration of the functional range of motion (ROM) of the ankle. Preservation of ankle motion may improve quality of life as evidenced by patient-reported outcome measures (PROMs). However, some studies have shown a lack of improvement of ankle range of motion after the postoperative recovery period, despite satisfactory motion being observed intra-operatively. The objective of this study was to radiographically compare intraoperative and pre-operative ankle range of motion. Methods: This single-center retrospective study compared 56 patients with an average age of 62.27 years who underwent primary TAR with one of four different implants between March and December 2019. 48% of patients had post-traumatic arthritis secondary to an ankle fracture, 50% had post-traumatic arthritis secondary to instability. Seventy-two percent of patients had an associated Achilles lengthening, 16% had an associated lateral ligament reconstruction procedure. Standardized weight-bearing maximum dorsiflexion and plantarflexion sagittal radiographs were obtained pre-operatively. In order to record intraoperative fluoroscopic imaging, the primary surgeon passively placed the ankle into maximum dorsiflexion and plantarflexion. Intraoperatively, the neutral lateral position of the ankle was determined after the replacement when the talus was in perfect lateral view. All angular measurements were made using the PACS system (Picture Archiving and Communication System). The change in range of motion was analyzed using a paired t-test with a significance level of 0.05. Results: The intraoperative range of motion increased significantly for all measures when compared to the pre-operative range of motion. The average pre-operative global arc of motion significantly increased from 20.21 degrees to 38.49 degrees intra- operatively (p=2.45x10-18, t(55)=2.00). The average pre-operative plantar flexion significantly increased from 12.80 degrees to 25.50 degrees intra-operatively (p=2.56x10-15, t(55)=2.00). The average pre-operative dorsiflexion significantly increased from 7.28 degrees to 13.35 degrees intra-operatively (p=4.68x10-6 t(55)=2.00). Patients who had an Achilles lengthening had an average increase in the global arc of motion of 18.78 degrees; patients who did not have an Achilles lengthening had an average increase of 17.02 degrees (p=0.562, t(31)=2.04). Overall, 93% of patients increased their range of motion after their total ankle replacement. Conclusion: This study demonstrates notable improvement in ankle range of motion intraoperatively following total ankle replacement, especially in plantarflexion. Total Ankle Replacement provides an improvement in the functional range of motion of the ankle intraoperatively, suggesting that the loss of motion observed in previous studies may occur during the postoperative period. The present study may help inform and adjust the postoperative rehabilitation protocol after total ankle replacement in order to avoid losing the amplitude of motion gained during the operation.